Nuclear safeguards, security and nonproliferation : achieving security with technology and policy - Doyle, James E. (Oxford : Butterworth-Heinemann, 2019)
This is a comprehensive reference that covers cutting-edge technologies used to trace, track, and safeguard nuclear material. Topics covered include the security of nuclear facilities and material, the illicit trafficking of nuclear materials, improvised nuclear devices and how to increase global nuclear transparency.
Includes bibliographical references and index.
Keywords: Nuclear facilities -- Security measures; Nuclear nonproliferation; Case studies